2006
DOI: 10.1103/physrevb.74.245307
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical evidence for a hydrogen stabilizedc(2×2)reconstruction of the P-rich InP(001) surface

Abstract: The formation of hydrogen bonds was investigated on the P-rich InP͑001͒ surface employing attenuated total-reflection Fourier-transform infrared spectroscopy, low-energy electron diffraction, and total-energy density-functional theory calculations. Strong evidence was found for a c͑2 ϫ 2͒-2P-3H reconstruction with a higher hydrogen coverage than is characteristic for the metal-organic chemical-vapor deposition prepared hydrogen-stabilized ͑2 ϫ 2͒-2D-2H surface. The new surface reconstruction was formed upon ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…1 obeys the electron counting rule and contains more P-H bonds than the unit cell (2x2)-2D-2H [2]. Recently, first principles calculations have confirmed that the former unit cell also forms a stable phase, however, at a much higher concentration of hydrogen [4]. The corresponding phase transition was, however, not observed when the hydrogen pressure was increased to the maximum 900 mbar that is available in our MOCVD reactor.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…1 obeys the electron counting rule and contains more P-H bonds than the unit cell (2x2)-2D-2H [2]. Recently, first principles calculations have confirmed that the former unit cell also forms a stable phase, however, at a much higher concentration of hydrogen [4]. The corresponding phase transition was, however, not observed when the hydrogen pressure was increased to the maximum 900 mbar that is available in our MOCVD reactor.…”
Section: Resultsmentioning
confidence: 76%
“…The FTIR spectra were measured with a Bruker Optics IFS66v spectrometer, other experimental details can be found below and in references [3,4]. Polarized and orientation dependent FTIR signals have confirmed the formation of the (2x2)-2D-2H unit cell [3] for the P-rich ordered InP(100) surface grown in an MOCVD reactor.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations